Robust Preimplantation Genetic Testing Strategy for Myotonic Dystrophy Type 1 by Bidirectional Triplet-Primed Polymerase Chain Reaction Combined With Multi-microsatellite Haplotyping Following Whole-Genome Amplification - Lian, Mulias; Lee, Caroline G.; Chong, Samuel S. (Frontiers in Genetics, 2019)
Myotonic dystrophy type 1 (DM1) is caused by expansion of the DMPK CTG trinucleotide repeat. Disease transmission to offspring can be avoided through prenatal diagnosis or preimplantation genetic testing for monogenic disorders (PGT-M). We describe a robust strategy for DM1 PGT-M that can be applied to virtually any at-risk couple. This strategy utilizes whole-genome amplification, followed by triplet-primed PCR (TP-PCR) detection of expanded DMPK alleles, in parallel with single-tube haplotype analysis of 12 closely linked and highly polymorphic microsatellite markers. Bidirectional TP-PCR and dodecaplex marker PCR assays were optimized and validated on whole-genome amplified single lymphoblasts isolated from DM1 reference cell lines, and tested on a simulated PGT-M case comprising a parent-offspring trio and three simulated embryos. Bidirectional DMPK TP-PCR reliably detects repeat expansions even in the presence of non-CTG interruptions at either end of the expanded allele. Misdiagnoses, diagnostic ambiguity, and couple-specific assay customization are further minimized by the use of multi-marker haplotyping, preventing the loss of potentially unaffected embryos for transfer.